Phosphoglucomutase comes into the spotlight. (13th March 2023) - Doello, Sofía; Forchhammer, Karl
Abstract : This article comments on: Ortega-Martínez P, Roldán M, Díaz-Troya S, Florencio FJ . 2023. Stress response requires an efficient glycogen and central carbon metabolism connection by phosphoglucomutases in cyanobacteria. Journal of Experimental Botany 74, 1532–1550